Perancangan User Experience Aplikasi Thriftshop di Masa Pandemi berbasis Mobile menggunakan Metode Design Thinking - Atikah Nabila; Ratih Kartika Dewi; Riswan Septriayadi Sianturi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
At the beginning of 2020, Covid-19 attacked the whole world and claimed many lives, thus limiting community activities, one of which was direct buying and selling activities. Based on the survey, researchers found that as many as 95.6% of buyers found it difficult to visit a thrift shop during the pandemic. Furthermore, as many as 91.3% of buyers also find it difficult to find suitable used clothes at affordable prices. Then, as many as 73.9% of buyers feel that a lot of time is wasted when buying used clothes directly at a thrift shop. Finally, as many as 69.5% of buyers find it difficult to find a place to sell used clothes. Therefore, to overcome the difficulties felt by buyers, it is necessary to design a mobile application user experience to help make it easier for buyers to make purchases of used clothes online. The design of user experience in this study uses the design thinking method which consists of 5 stages, namely empathize, define, ideate, prototype, and test. The last stage is testing using usability testing to test aspects of effectiveness, efficiency aspects, and aspects of user satisfaction. The test results on the design of the application solution that have been made show that the effectiveness aspect test gets 100% results, the efficiency aspect test gets a result of 0.0724 goals/sec, and the satisfaction aspect test gets a System Usability Scale (SUS) score of 94 out of 100. The SUS score indicates that the solution design from the thriftshop application user experience design is in the grade A category, adjective rating excellent, and also in the acceptable category.